2017
DOI: 10.1590/0001-3765201720170076
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the axial skeleton of seven bat genera (Chiroptera: Phyllostomidae)

Abstract: Here we present detailed descriptions and comparisons of the axial skeleton of seven species of bats belonging to five subfamilies of Phyllostomidae of different trophic guilds. The material examined consisted of 34 complete skeletons of seven species. For five of the studied species, previous descriptions have not been conducted, and for the vampires only limited information is available, so that descriptions for these species are here completed. The axial skeleton has characters that allow grouping of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
(52 reference statements)
0
10
0
Order By: Relevance
“…When diagnosing the bat families and searching for general trends in shape space, a common theme revealed here was the grouping of taxa that are not closely related under morphologies with an apparent functional meaning (Gaudioso et al. ). This was well‐illustrated by the proximity of Desmodontinae, Mystacinidae, and Molossidae, from both categorical and quantitative (robusticity) data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When diagnosing the bat families and searching for general trends in shape space, a common theme revealed here was the grouping of taxa that are not closely related under morphologies with an apparent functional meaning (Gaudioso et al. ). This was well‐illustrated by the proximity of Desmodontinae, Mystacinidae, and Molossidae, from both categorical and quantitative (robusticity) data.…”
Section: Discussionmentioning
confidence: 99%
“…), but also due to the ecological diversity reported for some of its components (Gaudioso et al. ). More specifically, our aims in this study are: (1) to describe femoral anatomical features and diagnose bat families; (2) to explore major quantitative trends in the morphology of the femur; and (3) to revisit allometric patterns in femur main dimensions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also showed that the development of the vertebral column of bats deviates from both the non-volant mammals and birds. In comparison to other mammals, unique morphological features found in the vertebral column of bats have been linked to the roosting and feeding ecology of the species [99]. Our findings of sequence heterochrony in the vertebral column indicate that the morphological patterns found in this region in previous studies could have an ontogenetic basis, originating during the prenatal development of the skeleton [47, 99].…”
Section: Discussionmentioning
confidence: 53%
“…Like in most flying birds, bats have a keel on the sternum where the large pectoral muscles attach ( Gaudioso et al, 2017 ). Gross anatomy and electromyography studies have also identified numerous muscles in the arm and forearm of bats with roles in powering wing movement and controlling wing shape and orientation during flight ( Hermanson and Altenbach, 1981 ).…”
Section: Anatomic and Physiologic Features Of Insect Bird And Bat Fmentioning
confidence: 99%